2008
DOI: 10.1007/s10828-008-9018-0
|View full text |Cite
|
Sign up to set email alerts
|

Dutch scrambling and the nature of discourse templates

Abstract: The so-called cartographic approach to discourse-related word-order variation is based on the idea that particular interpretations-say, contrastive focusare licensed in the specifier of particular functional projections-say, a focus phrase. In this paper we present arguments against this view based on scrambling in Dutch. We discuss a range of implementations of the cartographic approach and show that they are either too weak, in that they cannot generate all the word orders found in Dutch, or too strong, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 35 publications
(27 reference statements)
1
105
0
1
Order By: Relevance
“…This indicates that the subject must realize old information: the more topical the subject, the more grammatical the sentence. As is fairly well-established, information-structurally, a topic needs to precede a focus (see Prince 1981, Reinhart 1981, Vallduví 1992, Lambrecht 1994, Haji?ová, Partee, and Sgall 1998, Tomioka 2007, Neeleman and Van de Koot 2008. Thus, in order to be topical, the subject must move across the focused adverb, by adjoining to IP again or by moving to the specifier of a higher functional projection, presumably some TopP.…”
Section: (19) Icelandicmentioning
confidence: 99%
“…This indicates that the subject must realize old information: the more topical the subject, the more grammatical the sentence. As is fairly well-established, information-structurally, a topic needs to precede a focus (see Prince 1981, Reinhart 1981, Vallduví 1992, Lambrecht 1994, Haji?ová, Partee, and Sgall 1998, Tomioka 2007, Neeleman and Van de Koot 2008. Thus, in order to be topical, the subject must move across the focused adverb, by adjoining to IP again or by moving to the specifier of a higher functional projection, presumably some TopP.…”
Section: (19) Icelandicmentioning
confidence: 99%
“…In (51) The answer in (52) is possible only if a contextually given set of Fritz and Irina (and Karl) may be accommodated, i.e., the subject Irina may be interpreted as given. Otherwise, Irina is newly introduced (see also Neeleman and van de Koot 2008), and as such it obligatorily receives a structural accent, which leads to an intervention effect with the fronted focused object. 34 Recall that multiple wh-contexts where both elements are not contextually given do not allow inversion.…”
Section: Multiple Foci/contrastive Topicsmentioning
confidence: 99%
“…Later research has further suggested that A-movement is also required for semantic reasons for negation (e.g. Haegeman 1995 andChristensen 2005), quantified expressions (Jónsson 1996 andSvenonius 2000), and focus and topic constructions (Neeleman & Van de Koot 2008). A language where we can readily detect all these movements is Hungarian; see the first six chapters in É.…”
Section: Full Interpretationmentioning
confidence: 99%